Limit analysis on FRP-strengthened RC members - D. De Domenico; A.A. Pisano; P. Fuschi (Fracture and Structural Integrity)
Reinforced concrete (RC) members strengthened with externally bonded fiber-reinforced-polymer (FRP) plates are numerically investigated by a plasticity-based limit analysis approach. The key-concept of the present approach is to adopt proper constitutive models for concrete, steel reinforcement bars (re-bars) and FRP strengthening plates according to a multi-yield-criteria formulation. This allows the prediction of concrete crushing, steel bars yielding and FRP rupture that may occur at the ultimate limit state. To simulate such limitstate of the analysed elements, two iterative methods performing linear elastic analyses with adaptive elastic parameters and finite elements (FEs) description are employed. The peak loads and collapse mechanisms predicted for FRP-plated RC beams are validated by comparison with the corresponding experimental findings.